2022
DOI: 10.1002/wcms.1622
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐exascale HPC approaches for molecular dynamics simulations. Covid‐19 research: A use case

Abstract: Exascale computing has been a dream for ages and is close to becoming a reality that will impact how molecular simulations are being performed, as well as the quantity and quality of the information derived for them. We review how the biomolecular simulations field is anticipating these new architectures, making emphasis on recent work from groups in the BioExcel Center of Excellence for High Performance Computing. We exemplified the power of these simulation strategies with the work done by the HPC simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 229 publications
0
7
0
Order By: Relevance
“…The supercomputing infrastructure enabled rapid parallel processing, allowing researchers to evaluate an extensive library of antibody candidates within a short timeframe. The simulations provided valuable insights into the structural and functional characteristics of the designed antibodies, aiding in the selection of lead candidates for further experimental validation [71]. This study demonstrated how supercomputers can significantly expedite the design and optimization of therapeutic antibodies against COVID-19.…”
Section: Drug Discoverymentioning
confidence: 86%
“…The supercomputing infrastructure enabled rapid parallel processing, allowing researchers to evaluate an extensive library of antibody candidates within a short timeframe. The simulations provided valuable insights into the structural and functional characteristics of the designed antibodies, aiding in the selection of lead candidates for further experimental validation [71]. This study demonstrated how supercomputers can significantly expedite the design and optimization of therapeutic antibodies against COVID-19.…”
Section: Drug Discoverymentioning
confidence: 86%
“…In the era of exascale computing, 91,92 it is tempting to design molecular systems to study from organelles 9,93 to viruses 93,94 or even an entire cell. [95][96][97] Yet, the computing power necessary to simulate such large systems is still very huge and prevents one from reaching simulated timescales useful to decipher even simple phenomena such as the diffusion of large molecules 93 without even mentioning relevant biological time scales of milliseconds or longer.…”
Section: Discussionmentioning
confidence: 99%
“…Before presenting applications, it is important to first describe the methodological context. Methodological advances were driven by improvements both in computational power [8][9][10] and in experimental techniques capable of determining the structure of very large membrane protein assemblies [11][12][13][14]. It is currently possible to model both very large assemblies composed of millions of particles and very specific interactions between few atoms.…”
Section: -Methodological Development To Model β-Barrel Proteinsmentioning
confidence: 99%